PERANAN UPAH MINIMUM TERHADAP PERTUMBUHAN EKONOMI DAN PENYERAPAN TENAGA KERJA DI PROVINSI BALI - I GUSTI AYU MADE AGUNG MAS ANDRIANI PRATIWI (GANEC SWARA, 2023)
The absorption of labor in the Province of Bali over the past five years has experienced quite significant fluctuations, especially during the Covid-19 pandemic, because many workers were laid off and even experienced layoffs by their companies. This is shown through employment absorption in 2020 which has decreased significantly compared to previous years. Relatively current labor absorption is often associated with economic growth. The higher the level of economic growth in an area, the lower the unemployment rate and the higher the level of employment. This research is focused on discussing the description of labor absorption and economic growth associated with the minimum wage in the Province of Bali. The research objectives in this study were to determine 1) the effect of the minimum wage on economic growth; 2) the effect of minimum wages and economic growth on employment; and 3) the role of economic growth in mediating the effect of the minimum wage on employment in the Province of Bali. The approach used in this study is a quantitative approach. This research uses secondary data obtained from the Central Bureau of Statistics (BPS) of Bali Province. Panel data was used in this study by combining time series data from 2013-2021 and cross-sectional data from nine districts/cities in Bali Province. The data processing tools used are Microsoft Excel and SmartPLS. The results of the study show that: (1) the minimum wage has a direct and significant positive effect on economic growth; (2) the minimum wage has a direct and insignificant negative effect on employment; (3) economic growth directly has a positive and insignificant effect on employment; and (4) economic growth does not mediate the effect of the minimum wage on employment.